(untitled) (Educational Dimension, 2023)
This study delves into the theoretical examination, creation, and experimental testing of diverse instructional approaches aimed at introducing lyceum students to the fundamental principles of quantum informatics. Our research encompasses the following accomplishments: 1) A comprehensive analysis of relevant literature on the teaching of quantum informatics, both within Ukraine and internationally; 2) Theoretical grounding and development of the structure and content of competencies in the fundamentals of quantum informatics for lyceum students, incorporating insights from expert surveys and the European competence framework in quantum technologies; 3) Development of a robust structural and functional model for cultivating competencies in the fundamentals of quantum informatics; 4) Proposal of a methodological framework for teaching the fundamentals of quantum informatics to lyceum students through an optional course; and 5) Experimental validation of the efficacy of the developed methodology in enhancing students’ competency in the fundamentals of quantum informatics. Furthermore, we outline future scientific investigations pertaining to the quantum transformation of informatics education in schools.